Relation Between the Use of Gadget and the Visual Acuity in School Age Children in MI Tsamrotul Ulum Bungah Gresik - Musiah Musiah; Diah Fauzia Zuhroh (Indonesian Vocational Research Journal, 2022)
ABSTRACT Technology isdeveloping rapidly according to its era. One form of technology that is circulating is a gadget. The use of gadgets wrong and frequency the use ofexcessive gadget, of position that does not righ and antensty of the lighting not good, would have an impact on dreasing visual acuity. The purpose of the study was to analyze the relationship gadget use and decreased visual acuity in school age children. A method of the research approach by cross-sectional with the methods simple random sampling. The sample is 102 students. Data analysis with rank spearman test. The results of this study shawed that most of the respondents who frequently used gadgets as many as 26 (60,5%) experienced a decrease in visual acuity. And respondents who rarely use gadgets only 10(23,2%) expoertenced a decreare in visual acuity. The results of stastical tests indicate sig (2-taled) 0,000 < 0,05 which means that there is a significant relationship between gadget use and visual acuity. Conclusion the results of statistical test show that there is a relationship gadget use and visual acuity in school agechildren. Keyword : Gadgets, sharpness of vision